The Essence of Supply Chain Management of Corporate and Social Sector - Shetty, Vijetha S. (Prabandhan: Indian Journal of Management, 2010)
Retail, one of the largest sectors in the global economy, is going through a transition phase in India. Retailing has become a green pasture bearing a vast amount of untapped market potential which is eyed by the new as well as existing entrepreneurs. This suggests that the potential for growth is immense and modern retailing is poised for a mega change. Hitherto, dominated by the traditional formats in form of 'mom and pop' stores or the 'kiranas', with the 'shoppertainment' in vogue, there is a paradigm shift from the traditional (unorganized) to modern(organized) retail.. The country's retail sector presents a unique opportunity as consumption driven economy to investors across the globe to use India as a strategic hub. During an economic slowdown, there was an intense pressure on the retailers to cut costs so as to sustain profits. At present, when the bigwigs of the developed countries around the globe are facing economic slowdown, surprisingly, India's economy is poised for an exceptionally good growth rate of around 8%-9%. Again, the challenge in retail sector remains the same i.e. to cut costs so as to maximize profits. Hence, in order to be cost effective during recession, recovery or boom time, focus on a highly efficient supply chain is imperative to gain competitive edge. India can position itself as a lead player in Asia, if the retail sector here attains the competitive strengths by responding to the changing markets through supply chain. As the retail market matures, reverse logistics (RL) management also needs to be considered as an important supply chain strategy to cut costs and improve efficiency.